2019
DOI: 10.1080/09581596.2019.1693029
|View full text |Cite
|
Sign up to set email alerts
|

Global action, but national results: strengthening pathways towards better health outcomes for non-communicable diseases

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
5
0
2
Order By: Relevance
“…Whilst mandatory regulatory mechanisms are a stronger approach, there has been less systematic examination of their design. Magnusson and Patterson state that laws are a necessary mechanism to combat NCDs and meet global commitments such as the WHO Set of Recommendations and the Global Action Plan on NCDs [ 31 33 ]. However, legal capacity is lacking in many countries, and sharing best practices and lessons learned from other governments is imperative for capacity building [ 32 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst mandatory regulatory mechanisms are a stronger approach, there has been less systematic examination of their design. Magnusson and Patterson state that laws are a necessary mechanism to combat NCDs and meet global commitments such as the WHO Set of Recommendations and the Global Action Plan on NCDs [ 31 33 ]. However, legal capacity is lacking in many countries, and sharing best practices and lessons learned from other governments is imperative for capacity building [ 32 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the following report in 2018 by WHO, NCDs are important health concern in the Islamic Republic of Iran, whereby the annual death rate from NCDs represents about 82% of the total mortality in the country. [ 5 6 7 8 9 10 ] Reports provided by various organizations in Iran indicate that the daily consumption of salt intake is almost twice the level recommended by WHO. [ 11 12 13 ] Moreover, a research by the National Nutrition and Food Technology Research Institute (Iran) indicated that in 2016, the mean sodium intake level by adults in Tehran was more than 3,700 mg/day, which is considerably higher than the permitted level of sodium intake recommended by WHO, i.e ., 2,300 mg/day.…”
Section: Introductionmentioning
confidence: 99%
“…Magnusson and Patterson state that laws are a necessary mechanism to combat NCDs and meet global commitments such as the WHO Set of Recommendations and the Global Action Plan on NCDs. (25)(26)(27) However, legal capacity is lacking in many countries, and sharing best practices and lessons learned from other governments is imperative for capacity building. (26)(27)(28) For example, in Chile, policymakers had no relevant precedent to follow for technical development of the regulation and had to look to tobacco control laws for assistance.…”
Section: Introductionmentioning
confidence: 99%
“…(25)(26)(27) However, legal capacity is lacking in many countries, and sharing best practices and lessons learned from other governments is imperative for capacity building. (26)(27)(28) For example, in Chile, policymakers had no relevant precedent to follow for technical development of the regulation and had to look to tobacco control laws for assistance. (29) To advance the literature on the technical design of food marketing legislation, and to support governments around the world with legislative design, we aimed to describe the legislative approach from three governments (Chile, Canada and United Kingdom (UK)) that have introduced legislative Bills, two of which passed.…”
Section: Introductionmentioning
confidence: 99%